"An indelible mark" the response to participation in euthanasia and physician-assisted suicide among doctors: A review of research findings. Issue 1 (February 2020) - Kelly, Brian; Handley, Tonelle; Kissane, David; Vamos, Marina; Attia, John
Abstract: Introduction: The debate regarding euthanasia and physician-assisted suicide (E/PAS) raises key issues about the role of the doctor, and the professional, ethical, and clinical dimensions of the doctor-patient relationship. This review aimed to examine the published evidence regarding the response of doctors who have participated in E/PAS. Methods: Original research papers were identified reporting either qualitative or qualitative data published in peer-reviewed literature between 1980 and March 2018, with a specific focus on the impact on, or response from, physicians to their participation in E/PAS. PRISMA and CASP guidelines were followed. Results: Nine relevant papers met selection criteria. Given the limited published data, a descriptive synthesis of quantitative and qualitative findings was performed. Quantitative surveys were limited in scope but identified a mixed set of responses. Where studies measured psychological impact, 30–50% of doctors described emotional burden or discomfort about participation, while findings also identified a comfort or satisfaction in believing the request of the patient was met. Significant, ongoing adverse personal impact was reported between 15% to 20%. A minority of doctors sought personal support, generally from family or friends, rather than colleagues. The themes identified from the qualitative studies were summarized as: 1) coping with a request; 2) understanding the patient; 3) the doctor's role and agency in the death of a patient; 4) the personal impact on the doctor; and 5) professional guidance and support. Significance of results: Participation in E/PAS can have a significant emotional impact on participating clinicians. For some doctors, participation can contrast with perception of professional roles, responsibilities, and personal expectations. Despite the importance of this issue to medical practice, this is a largely neglected area of empirical research. The limited studies to date highlight the need to address the responses and impact on clinicians, and the support for clinicians as they navigate this challenging area.